Accounting history, a privileged way to approach historical research. An illustrative case: the war of France and the holy see against Spain, 1556-1559 - Hernández Esteve, Esteban (De Computis, Revista Española de Historia de la Contabilidad., 2010)
The international expansion of accounting history in the last fifteen or twenty years has really been impressive. It has reached a level that has opened a new stage of development, a stage that calls for a new conception of the discipline that lives up to the degree of maturity that it has reached. The new concept of accounting history has to view it not only as a study of the evolution of accounting and related matters, but as a privileged way to approach historical research as a whole. And that because all or almost all human activities have an economic aspect and therefore they need to keep accounts in one or other way. However most historical events, even the most important, have been described and interpreted without considering at all the possible existence of accounting registers related to them. Consequently there are thousands and thousands of account books and bundles of accounting records all over the world gathering the dust of ages, because they have been never touched by a historian’s hand. Practically the only historians that base their researches on account books are the accounting historians. Thus most of them, when practising archival research, do not limit themselves to search for the evolution and changes of accounting theories, techniques or practices. They go far beyond and explore the events and operations recorded in the account books attempting to place them into the correct context in order to find out their historical significance. They have it quite clear. What really is missing in this context is a formal statement of the authentic nature of accounting history -a sub-discipline of economic history- as a very effective way to research not only into economic subjects, but into every subject trough the accounting documentation kept because of its economic facets. The formulation of this statement is the main purpose of the present paper. And it wants to make clear the new conception of accounting history through an illustrative case: the war held by Henry II, king of France, and the Pope Paul IV against Philip II, king of Spain, in the years 1556-1559.